Legal Protection of Patent Rights in The Pharmaceutical Industry Concerning the Availability and Accessibility of Medications in Society - Kriston Kriston; Suarian Datupalinge; Adfiyanti Fadjar (Civiliza Publishing, 2026)
This study aims to analyze the legal protection of patent rights in the pharmaceutical industry and its implications for the availability and accessibility of medicines in the community. The research method used is normative legal research. The results show that the legal system in Indonesia has accommodated these balancing efforts through various mechanisms, such as compulsory licensing, government use of patents, and provisions in international agreements such as the TRIPS Agreement, which provide flexibility for countries under certain conditions. However, the implementation of these policies still faces various obstacles, both from regulatory and institutional aspects, as well as global pressures. These mechanisms allow countries to ensure the availability of affordable medicines for the community under certain conditions without having to completely ignore the rights of patent holders. In conclusion, legal protection of patent rights in the pharmaceutical industry must be implemented proportionally while still considering the public's right to health. Therefore, it is necessary to optimize the government's role in implementing policies that can ensure the availability and accessibility of medicines fairly, without hindering innovation in the pharmaceutical sector.